2016
DOI: 10.1111/ajt.13420
|View full text |Cite
|
Sign up to set email alerts
|

Ad Integrum Functional and Volumetric Recovery in Right Lobe Living Donors: Is It Really Complete 1 Year After Donor Hepatectomy?

Abstract: Julie Duclos and Prashant Bhangui are co-first authors.The partial liver's ability to regenerate both as a graft and remnant justifies right lobe (RL) living donor liver transplantation. We studied (using biochemical and radiological parameters) the rate, extent of, and predictors of functional and volumetric recovery of the remnant left liver (RLL) during the first year in 91 consecutive RL donors. Recovery of normal liver function (prothrombin time [PT] !70% of normal and total bilirubin [TB] 20 mmol/L), liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…The volume of the residual liver was ~50% of ESLV, and all donors recovered well following surgery, which indicated that the decrease in liver regeneration is a subclinical process; additionally, the residual liver function was able to meet the metabolic requirements. According to the literature, the recovery of donor liver volume was still incomplete at 1 year post-donation, accounting for 85% of the total preoperative volume; however, liver function had almost returned to normal (16).…”
Section: Discussionmentioning
confidence: 99%
“…The volume of the residual liver was ~50% of ESLV, and all donors recovered well following surgery, which indicated that the decrease in liver regeneration is a subclinical process; additionally, the residual liver function was able to meet the metabolic requirements. According to the literature, the recovery of donor liver volume was still incomplete at 1 year post-donation, accounting for 85% of the total preoperative volume; however, liver function had almost returned to normal (16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both serum total bilirubin and prothrombin time/INR are surely indices of liver function, but they are also influenced by several clinical factors that may alter the direct correlation between volumetric regeneration and function recovery. Finally, vLR after major hepatectomy shows complex kinetics that is mainly characterized by a sharp and steady volume increase in the first postoperative week up to the first postoperative month, followed by a slower regenerative rate during the subsequent 3 months, and a late long‐term stabilization up to 1 year after surgery . Therefore, a seriated volumetric assessment at different postoperative time points, rather than a single measurement normalized by a time interval, might be a more appropriate and reliable approach for vLR analysis.…”
mentioning
confidence: 99%
“…According to the literature, the recovery of donor liver volume was still incomplete at 1 year post donation, accounting for 85% of the total preoperative volume; however, liver function had almost returned to normal [19].…”
Section: Discussionmentioning
confidence: 99%